2013
DOI: 10.2478/acph-2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

The content of fagopyrin and polyphenols in common and tartary buckwheat sprouts

Abstract: Dried buckwheat herb is used in medicinal products whereas fresh green plant parts, especially sprouts, are consumed as a vegetable. The herb contains fagopyrins, which cause sensitivity to light after ingestion. The aim of this study was to investigate the impact of different growing conditions and the development phase on the content of fagopyrin and phenolic compounds in buckwheat sprouts. Total flavonoid and total phenol contents, fagopyrin content and antioxidant activity were determined spectrophotometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
0
29
0
3
Order By: Relevance
“…High content was found in the years with a drought and higher average monthly air temperature, and it can be concluded that these factors are the main cause of differences. Kreft et al (2013) and Lumingkewas et al (2015) also found that temperature and humidity have effect on concentration of phenol in buckwheat.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…High content was found in the years with a drought and higher average monthly air temperature, and it can be concluded that these factors are the main cause of differences. Kreft et al (2013) and Lumingkewas et al (2015) also found that temperature and humidity have effect on concentration of phenol in buckwheat.…”
Section: Resultsmentioning
confidence: 93%
“…Total phenols have a vital part in the protection of plants against high or low temperatures (Kreft et al, 2013), droughts (Lim et al 2012), UV radiation (Kreft et al,2003;Germ, 2004), pathogens and herbivores (Guo et al, 2011) and their high concentration in plants suggest to environmental stress factors (Stagnari, et al, 2017). The results in Table 3.…”
Section: Resultsmentioning
confidence: 98%
“…Ferulic acid and rutin were the major antioxidant compounds of buckwheat and existed mostly in the outer layers of grain. As a result, the outer layers of buckwheat grains with higher amount of phenolic compounds along with higher amounts of protein, lipid, ash and dietary fiber are considered to be good materials for cereal-based food processing with significant health benefits [12,25,26].…”
Section: Frap Methodsmentioning
confidence: 99%
“…Kvercetin-3-O-robinobiozid v kalicah tatarske ajde ni bil določen (Nam et al 2015). Kreft et al (2013) so ugotovili, da se večina fenolov nahaja v kotiledonih kalic tatarske ajde in navadne ajde. Liu et al (2008) pa so ugotovili, da imajo kalice tatarske ajde večjo skupno antioksidativno aktivnost kot kalice navadne ajde.…”
Section: Flavonoidiunclassified